2014
DOI: 10.1186/1471-2334-14-486
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibilities of Proteus mirabilis: a longitudinal nationwide study from the Taiwan surveillance of antimicrobial resistance (TSAR) program

Abstract: BackgroundLongitudinal nationwide data on antimicrobial susceptibility in Proteus mirabilis from different sources are rare. The effects of the revised Clinical and Laboratory Standards Institute (CLSI) β-lactam breakpoints on susceptibility rates and on detecting extended-spectrum β-lactamase (ESBL) and AmpC β-lactamase-producers in this species are also seldom evaluated. The present study analyzed data from the Taiwan Surveillance of Antimicrobial Resistance program to address these issues.MethodsIsolates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 30 publications
7
47
1
2
Order By: Relevance
“…In contrast, no dominant β-lactamase genes are carried by ICE Pmi Chn117, suggesting that the class A β-lactamase gene might have been obtained via horizontal gene transfer or recombination. In summary, our study reported multi-drug resistance, including the increasing prevalence of class A β-lactamase-producing P. mirabilis , which is consistent with the trends in Japan16, Taiwan39 and other reports2440. In conclusion, our results present abundant genetic diversity and multidrug resistance of ICEs carried by Proteus strains from both food sources and diarrhoeal patients.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, no dominant β-lactamase genes are carried by ICE Pmi Chn117, suggesting that the class A β-lactamase gene might have been obtained via horizontal gene transfer or recombination. In summary, our study reported multi-drug resistance, including the increasing prevalence of class A β-lactamase-producing P. mirabilis , which is consistent with the trends in Japan16, Taiwan39 and other reports2440. In conclusion, our results present abundant genetic diversity and multidrug resistance of ICEs carried by Proteus strains from both food sources and diarrhoeal patients.…”
Section: Discussionsupporting
confidence: 91%
“…strains, isolated from patients with bacteremia, were resistant to co-trimoxazole. High resistance to cotrimoxazole was reported also in another paper (Wang et al 2014). Among 158 examined strains isolated from blood samples during longitudinal nationwide study from the Taiwan Surveillance of Antimicrobial Resistance (TSAR) program, the resistance of P. mirabilis to co-trimoxazole was found in 65.2% strains.…”
Section: Discussionsupporting
confidence: 54%
“…Ahn et al (2017) confirmed that most P. mirabilis isolates from BSIs were susceptible to piperacillin with tazobactam (98.3%) and amikacin (93.5%). In the study by Wang et al (2014), 58.9-87.3% of P. mirabilis strains isolated from blood samples were susceptible to gentamicin and amikacin, respectively. This is in agreement with the present results.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…During the collection year, isolates were collected from July to September from 25–28 regional hospitals and medical centers located in different geographical regions of Taiwan. Detailed collection protocol has been published previously45. All isolates were stored at −70 °C.…”
Section: Methodsmentioning
confidence: 99%